2022
DOI: 10.1007/s11837-022-05180-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Curcumin-Loaded Electrospun Nanofibers and their Application in Modern Medicine

Abstract: Herbal drugs are safe and show significantly fewer side effects than their synthetic counterparts. Curcumin (an active ingredient primarily found in turmeric) shows therapeutic properties, but its commercial use as a medication is unrealized, because of doubts about its potency. The literature reveals that electrospun nanofibers show simplicity, efficiency, cost, and reproducibility compared to other fabricating techniques. Forcespinning is a new technique that minimizes limitations and provides additional adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 135 publications
0
30
0
Order By: Relevance
“…The Cur drug affects viscosity more than conductivity. This increased solution viscosity led to increased average fiber diameters by 130 ± 10 and 150 ± 15 nm for nanofibers with 1 and 3 wt% Cur, respectively (Mitra et al, 2022).…”
Section: Scanning Electron Microscope Images Of Samplesmentioning
confidence: 98%
“…The Cur drug affects viscosity more than conductivity. This increased solution viscosity led to increased average fiber diameters by 130 ± 10 and 150 ± 15 nm for nanofibers with 1 and 3 wt% Cur, respectively (Mitra et al, 2022).…”
Section: Scanning Electron Microscope Images Of Samplesmentioning
confidence: 98%
“…Drug delivery issues including instability and hydrophobicity are solved using polymer-based nanofibers whose benefits include stability, solubility, and drug storage. 36 This method uses solid materials or solutions that are melted into spinnerets and spun into nanofibers by centripetal forces. There is no need for solvent recovery because no solvent is used.…”
Section: Methods Of Fabrication Of Wound Dressings and Hydrogelsmentioning
confidence: 99%
“…125 Curcumin nanofibers also support effective treatments of cancers and wound healing. 126 Some polymers used to make medical applications nanofibers include PU, PHBV, poly(lactic-co-glycolic acid) (PLGA), Bombyx mori silk, and zein silk. Owing to their fascinating features, PLA, poly(-caprolactone) (PCL), and polyvinyl alcohol (PVA) seem to be the most usually utilized polymers to fabricate nanofibers.…”
Section: Diabetic Wound Healingmentioning
confidence: 99%
“…One study reported that nanofibers combined with SiO 2 or SiO 2 ‐based nanoparticles promote diabetic wound repair by activating associated pathways 125 . Curcumin nanofibers also support effective treatments of cancers and wound healing 126 . Some polymers used to make medical applications nanofibers include PU, PHBV, poly(lactic‐ co ‐glycolic acid) (PLGA), Bombyx mori silk, and zein silk.…”
Section: Wound Healingmentioning
confidence: 99%